Dampak pembangunan Yogyakarta international airport di daerah rawan bencana tsunami dengan dukungan sistem informasi geografis - Ilham Satria; Djati Mardiatno; Evita Hanie Pangaribowo (Universitas Gadjah Mada, 2023)
The construction of a new airport in tsunami disaster prone area in Kulon Progo Regency has been impacting in land use and land value. The changes in land use will impact on changing tsunami hazard model. This research aims to analyze the impact of a new airport on physical changes and land value changes in Temon District with geographic information system. The research begins with inventory of spatial data from various agencies. Multi-temporal image interpretation is resulted in 2015 and 2020 land use maps. Physical changes and tsunami models analysis were carried out using spatial analysis in ArcGIS. The making land value change maps using 2015 and 2021 land value zone maps. The analysis effect of new airports and tsunami hazard using multiple linear regression. Data validation was carried out by sampling techniques and field surveys. The results of spatial analysis is physical growth from 2015-2020 covering an area 418,019 m² and loss of a built area 149,261 m². The changes in the tsunami model from 2015-2020 increased by 118,740 m². The changes in land value from 2015-2021 is increasing the average value of Rp. 1,317,088/ meter² or 652%. The results of multiple linear regression analysis and community interviews concluded that the existence of an airport is very influential on increasing land value compared to the effect of tsunami vulnerability.